Yolk-shell-structured zinc-cobalt binary metal sulfide @ N-doped carbon for enhanced lithium-ion storage. (October 2019) - Wei, Xiujuan; Zhang, Yanbo; Zhang, Bingkai; Lin, Zhan; Wang, Xuanpeng; Hu, Ping; Li, Shenglong; Tan, Xin; Cai, Xinyin; Yang, Wei; Mai, Liqiang
Abstract: Owing to high capacity, low cost, and environmental benignity, transition-metal sulfides have attracted increasing attention as potential anode materials for lithium-ion batteries (LIBs). However, their practical application is impeded by poor cycling stability and rate capability due to large volume change and sluggish kinetics. Here, a yolk-shell structured zinc-cobalt binary metal sulfide @ N-doped carbon composite (Zn-Co-S@N-C) with enhanced lithium storage is reported. In this composite, unique porous yolk-shell structure provides short Li + /e − diffusion distance and offers sufficient void space to accommodate volume variation during the Li + insertion/extraction process. The presence of N-doped carbon matrix not only enhances electron transfer kinetics, but also improves structural stability. Moreover, bimetallic sulfides enhance electrochemical reactivity for superior lithium storage and mitigate the formation of by-products. The resulting Zn-Co-S@N-C anode exhibits significantly enhanced cycling stability (667.7 mAh g −1 after 300 cycles at 1000 mA g −1 ) and rate capability (332.2 mAh g −1 at 5000 mA g −1 ). Graphical abstract: A yolk-shell structured zinc-cobalt binary metal sulfide @ N-doped carbon composite (Zn-Co-S@N-C) with enhanced lithium storage is reported.Image 1 Highlights: Yolk-shell-structured Zn-Co-S@N-C composites are synthesized with outstanding structural stability and excellent cycling and rate performance. The intrinsic reasons for excellent cycling stability are confirmed by both the experimental and theoretical calculation analyses.